Hubungan Peran Tenaga Kesehatan dan Pengetahuan Ibu Terhadap Motivasi Pemberian Imunisasi PCV Pada Bayi Usia 0-11 Bulan di Wilayah Kerja UPT Puskesmas Poris Gaga Lama Kota Tangerang Tahun 2024 - Fatimah, Siti Nurul; Rindu, Rindu; Putri, Magdalena Tri (Jurnal Ilmiah Global Education, 2024)
Pneumonia is a disease caused by infection with the bacteria Streptococcus pneumoniae or pneumococcus. This disease attacks the respiratory tract and can infect the lungs. The lungs consist of small sacs called alveoli, which fill with air when healthy people breathe. When a person has pneumonia, the alveoli fill with pus and fluid, which makes breathing painful and limits oxygen intake. WHO data for 2022 states that pneumonia killed 740,180 children under 5 years of age in 2019, accounting for 14% of all deaths in children under 5 years but 22% of all deaths in children aged 1 to 5 years (World Health Organization, 2022). In the 2021 health profile, national data, the percentage of toddlers affected by pneumonia was 31.4%. One way to prevent the occurrence of pneumonia in children is the use of the Pneumococcal Conjugate Vaccine (PCV) which is able to provide more long-lasting and effective protection for children. Therefore, the aim of this research is to determine the relationship between the role of health workers and maternal knowledge regarding motivation for providing PCV immunization to babies aged 0-11 months, especially in the working area of ​​the UPT Poris Gaga Lama Health Center, Tangerang City in 2023